Análisis del impacto económico que representa la salida de correos del Euador. - Pelaez Campoverde, Raul Alberto (My University, 2021)
The following research work shows the trajectory through time of Correos del Ecuador, and as small problems have led to the cessation of all its functions in ecuadorian territory. In this case taking an analytical point of view with data provided by the press releases of this and taking into account its main competitors in the El Oro area, It should be noted that these decisions are made by a decree presented in 2020 by the former president of the republic Lenin Moreno, who assumes the closure of Correos del Ecuador because it did not generate profits for the country, resulting in an increase in the unemployment rate in the territory. Ecuadorian. Consequently, and for all the reasons stated above, this problem has allowed a boom in telecommunications, thus allowing everything to be done with the use of information and communication technology (ICT). At the same time, it allows the private sector to monopolize the commercial messaging and courier market, facilitating commercial services to the national territory through the services of companies such as DHL, Geomil, among others.
El siguiente trabajo investigativo muestra la trayectoria a través del tiempo de Correos del Ecuador, y como pequeños problemas han desembocado en el cese de todas sus funciones en el territorio ecuatoriano. Por tal motivo tomando un punto de vista analítico con datos proporcionados por los boletines de prensa de esta y tomando en cuenta sus principales competidores en la zona de El Oro, cabe resaltar que se toma estas decisiones por un decreto presentado en el 2020 por el expresidente de la república Lenin Moreno, quien asume el cierre de Correos del Ecuador porque no generaba ganancias al país, dando como resultado el aumento de la tasa de desempleo al territorio ecuatoriano. Por consiguiente y por todas las razones expuestas anteriormente esta problemática ha permitido un auge a las telecomunicaciones, permitiendo así que todo se realice con el uso de la tecnología de información y comunicación (TIC). A su vez permite al sector privado acaparar el mercado comercial de mensajería y courier, facilitando los servicios comerciales al territorio nacional a través de servicios de empresas como Dhl, Geomil, entre otros.
Keywords: ECONOMÍA; IMPORTACIÓN; EXPORTACIÓN; MENSAJERÍA